Static Shear Strength of Single-Lap Joint Using Eggshell-Toughened Epoxy as Adhesive Agent - Fong, Collin; Chin, Desmond Daniel; Ahmad, Mohd Hilton (International Journal of Integrated Engineering, 2023)
Eggshells are daily food waste in every household and are disposed of in landfills, producing environmental issues, and their decomposition has generated an unpleasant odour. Eggshell powder is made of finely crushed particles and is suitably applied as a filler in thermoset polymers such as epoxy resin to improve their mechanical properties. The shear strength of toughened epoxy with eggshell powder (TEEP) is studied. Single-lap joint (SLJ) shear tests were conducted to investigate the shear strength of the SLJ bonded with different volume fractions of TEEP. For this purpose, the eggshells were dried and crushed into particles of size 150?m. The volume fraction of eggshell powder in the epoxy resin is 0%, 2.5%, 5%, and 10% by volume. The epoxy resin system was made of EPIKOTE Resin 828 and Hardener 651 with a mixing ratio of 5:2 by volume. The results show that the ultimate joint strength greatly depended upon overlap length and filler volume fractions. The improvement was up to 72.7% and 39.9%, with the longest overlap length and 10% TEEP fraction. Hence, an overlap length of 38.1 mm and a 5% eggshell volume fraction gave the ultimate optimum strength of 5.045 kN.